Olive Oil can be a Useful Remedy to Prevent Osteoporosis - Basharat, Shahnai; Gilani, Syed Amir; Qamar, Muhammad Mustafa; Ali, Muhammad; Basharat, Benazir; Murtaza, Mian Anjum (Journal of Liaquat University of Medical & Health Sciences, 2019)
Osteoporosis is the major public health issue worldwide. It is the most common bone porosity, especially in women, in which elder people are more susceptible to skeletal delicacy and fracture and is caused when the skeletal mass and microarchitecture degrades with aging. Age, deficient bone growth, early menopause, and oxidative stress are the factors associated with the possible incidence of osteoporosis. Approximately 70 million people around the world have gotten affected by this disease. Olives and olive oil have a global recognition as a healthy food and the reason is the phenolic components present in it. The benefits of olives and olive oil included; anti-inflammatory properties and reduces oxidative stress. Oleuropein, hydroxytyrosol, and tyrosol prevent the development of multinucleated osteoclasts. Oleuropein intake has beneficial effects against bone loss that are linked with osteoporosis and aging because oleuropein works by increasing the generation of osteoblasts and by decreasing the development of fat cells. Olive oil can be correlated to a lower occurrence of osteoporosis and correspondingly reduced fracture risk. Mediterranean diet can be helpful in decreasing the incidence of osteoporosis. This review aims to address the role of olive oil in the prevention of osteoporosis.